The Relationship of Pregnant Women's Decision Making via Internet with Pregnancy Stress and Prenatal Attachment - Kurt, Nuray; Yılmaz, Ayşe Nur; Kök, Gamze (Bingöl Üniversitesi, 2024)
The study was conducted to evaluate the relationship between pregnant women's decision-making via internet and pregnancy stress and prenatal attachment. The research is cross-sectional and correlational. The sample of the study consisted of 271 pregnant women living in a province in eastern Turkey. The data were collected with the ‘Personal Information Form’, ‘Internet Decision Making Scale in Pregnancy (IDIPS)’, ‘Pregnancy Stress Rating Scale (PSRS)’ and ‘Prenatal Attachment Inventory (PBI)’. In the study, the mean total score of the pregnant women was 32.00±7.98, the mean total score of PSRS was 38.41±25.42 and the mean total score of PBI was 64.28±10.70. It was determined that there was a statistically positive and weakly significant relationship between the mean score of the IDIPS and the mean score of the PSRS (r=0.214; p= 0.000), a statistically positive and weakly significant relationship between the mean score of the IDIPS and the mean score of the PBI (r=0.233; p= 0.000), and a statistically negative and weakly significant relationship between the mean score of the PSRS and the mean score of the PBI (r=-0.083; p= 0.000). When the significance tests of the regression coefficients were taken into consideration, it was seen that PBI and PSRS were significant predictors of pregnant women's decision-making via internet. It was determined that as the level of pregnant women's decision-making via internet increased, their stress levels increased, and as the stress level increased, their prenatal attachment levels decreased significantly. It was determined that the prenatal attachment levels of pregnant women increased as the level of decision-making via the internet increased.

Çalışma, gebelerin internet yoluyla karar alma durumlarının gebelik stresi ve prenatal bağlanmayla ilişkisini değerlendirmek amacıyla yapılmıştır. Araştırma kesitsel ve ilişki arayıcı tiptedir. Araştırmanın örneklemini, Türkiye’nin doğusunda bulunan bir ilde yaşayan 271 gebe oluşturmuştur. Veriler, “Kişisel Tanıtım Formu”, “Gebelikte İnternet Yoluyla Karar Alma Ölçeği (GİYKAÖ)”, “Gebelikte Stresi Değerlendirme Ölçeği (GSDÖ)” ve “Prenatal Bağlanma Envanteri (PBE)” ile toplanmıştır. Araştırmada gebelerin GİYKAÖ toplam puan ortalaması 32.00±7.98, GSDÖ toplam puan ortalaması 38.41±25.42 ve PBE toplam puan ortalaması 64.28±10.70 olarak belirlenmiştir. Gebelerin; GİYKAÖ puan ortalaması ile GSDÖ puan ortalaması arasında istatistiksel olarak pozitif yönde zayıf düzeyde önemli bir ilişki olduğu (r=0.214; p= 0.000), GİYKAÖ puan ortalaması ile PBE puan ortalaması arasında istatistiksel olarak pozitif yönde zayıf düzeyde önemli bir ilişki olduğu (r=0.233; p= 0.000), GSDÖ puan ortalaması ile PBE puan ortalaması arasında istatistiksel olarak negatif yönde zayıf düzeyde önemli bir ilişki olduğu belirlenmiştir (r=-0.083; p= 0.000). Regresyon katsayılarının anlamlılık testleri göz önüne alındığında, gebelerin internet yoluyla karar alma durumları üzerinde PBE ve GSDÖ’nün anlamlı yordayıcısı olduğu görülmüştür. Gebelerin internet yoluyla karar alma düzeyleri arttıkça stres düzeylerinin arttığı, stres düzeyi arttıkça prenatal bağlanma düzeylerinin önemli düzeyde azaldığı belirlenmiştir. Gebelerin internet yoluyla karar alma düzeyleri arttıkça prenatal bağlanma düzeylerinin arttığı tespit edilmiştir.
Gebelerin İnternet Yoluyla Karar Alma Durumlarının Gebelik Stresi ve Prenatal Bağlanmayla İlişkisi
Keywords: Midwifery (Other); Ebelik (Diğer)